2010
DOI: 10.1021/je100794k
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of H2S in Ionic Liquids 1-Ethyl-3-methylimidazolium Hexafluorophosphate ([emim][PF6]) and 1-Ethyl-3-methylimidazolium Bis(trifluoromethyl)sulfonylimide ([emim][Tf2N])

Abstract: The solubility of hydrogen sulfide gas in ionic liquids (ILs) 1-ethyl-3-methylimidazolium hexafluorophosphate ([emim][PF 6 ]) at temperatures from (333.15 to 363.15) K and 1-ethyl-3-methylimidazolium bis(trifluoromethyl)sulfonylimide ([emim][Tf 2 N]) at temperatures ranging from (303.15 to 353.15) K and pressures up to about 2.0 MPa was measured using a volumetric based static apparatus. The solubility data were correlated using two models: the Krichevsky-Kasarnovsky (KK) equation, and the extended Henry's law… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(69 citation statements)
references
References 29 publications
3
66
0
Order By: Relevance
“…The Krichevsky-Kasarnovsky equation has been widely applied to calculate the solubility of gases in liquid solvents up to high pressures [3235]. This equation can be described as follows [36]: lnf2(T,P)x2=lnH2P1S+trueV¯2(PP1S)RT…”
Section: Resultsmentioning
confidence: 99%
“…The Krichevsky-Kasarnovsky equation has been widely applied to calculate the solubility of gases in liquid solvents up to high pressures [3235]. This equation can be described as follows [36]: lnf2(T,P)x2=lnH2P1S+trueV¯2(PP1S)RT…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21] Because of their attractive features such as negligible volatility, good thermal stability and tunable functionality, many experimental and theoretical studies have been performed to explore the properties of diverse ILs towards the removal of H 2 S. 22,23 For example, Jalili et al 24,25 reported a plenty of solubility data of H 2 S in a variety of imidazolium-based ILs in a wide range of temperature and pressure, and found that H 2 S solubility in 1-butyl-3-methylimidazoliumbased ILs follows the order: [Tf 2 N] ->[PF 6 ] ->[BF 4 ] -. Sakhaeinia et al 26 showed that the solubilities of H 2 S in 1-(2-hydroxyethyl)-3-methyl-imidazolium-based ILs are greater than those 4 of CO 2 and the number of trifluoromethyl (-CF 3 ) groups can affect the solubility of both gases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the removal of H 2 S from industrial gas and oil streams is an essential step because of its undesirably high toxicity and corrosiveness [5]; thus, the application of ILs for H 2 S removal purposes requires knowledge of the H 2 S solubility in ILs. Although experimental measurements are broadly available and can already provide some insights into the understanding of gas solubility in ILs [5][6][7][8][9][10][11][12][13][14][15], such measurements are often difficult, time-consuming and expensive. It is thus desirable to develop theoretical models that are able to estimate the gas solubility in ILs over a wide range of system conditions.…”
Section: Introductionmentioning
confidence: 99%